A Conceptual Framework for Emotional Connection Towards E- learning Mobile Application Design for Children. - Magrizef Gasah; Aslina Baharum (2018)
People usually tend to rely on their emotion in making a decision or doing something important in their lives. This emotion could affect how they view things around them and their decision every day such as buying a product, learning, communicating and memorizing. The user interface design could also do the same to users based on the emotional design implemented in the design and the emotional connection created by the designer that the designer wanted the user to feel. This paper discusses how to create the emotional connection design that could be applied to e-learning application for children within the age of 4 to 5 years old. This is to ensure that the children will feel a positive emotion and experience towards learning. To create the positive emotional connection in the mobile application eLearning some literature review in emotional interface design needs to be identified. The theory of the emotional interface design will be confirmed by the expected user through some data collection using a qualitative method. Last but not least, the result of the data collection will create a guideline for the emotional interface and for future works.